URGENSI PERAN PENGADILAN DALAM MEMBERIKAN PELAYANAN BANTUAN HUKUM TERHADAP ORANG MISKIN SESUAI UNDANG-UNDANG NOMOR 16 TAHUN 2011 TENTANG BANTUAN HUKUM - Nasution, Isnandar Syahputra (Jurnal Hukum dan Peradilan, 2015)
Implementation of Legal Aid Post (Posbakum) by the District Court includes three (3) the scope of legal services in accordance with the provisions contained in the Perma No. 1 Year 2014. Those 3 scopes are services of fee waiver, and the holding of the trial outside the court buildingÂ and providing Posbakum Court. In connection with the implementation of this Posbakum actually State Court only provides room facilities to Posbakum for three Legal Aid Provider or accredited lawyers organization. As for the legal aid fund handling each case will be filed by the Court through the Lokal Office of Kemenkumham. However, this does not mean that the facilitator function can be ignored, considering this Posbakum takes place in the Court, it is noteworthy that there is a special mandate from the State Officials to the Court in order to succeed the free legal services for the poor. Therefore, it can also be expected that the presence of the Posbakum in the Court can erode the negative and scary stigma on the Court for the general public. Keywords: Court, Legal Aid, the Poor